Influences of the steel plate on the running-in behavior of wet multi-plate clutches Einflüsse der Stahllamelle auf das Einlaufverhalten von Lamellenkupplungen - Völkel, Katharina; Pflaum, Hermann; Stahl, Karsten (Forschung Im Ingenieurwesen-Engineering Research, 2019)
Wet multi-plate clutches are relevant components of modern drivetrain applications, not only in terms of function but also safety and comfort. Especially at the beginning of their lifetime, characteristics of the steel plate as a result of manufacturing may influence the friction- and running-in behavior. Distinct changes of the friction behavior can occur and make the actuation of the clutch challenging. This contribution describes the typical running-in behavior of wet multi-plate clutches and gives a general definition for running-in of clutches. Based on a newly introduced test method, the running-in behavior of different tribological systems from AT and DCT applications were investigated systematically. The presented results focus on the effect of different steel plate variants (material and surface structure) on the running-in behavior.
CRIS-Team Scopus Importer:2025-05-19